Effect of a pediatric fruit and vegetable prescription program on child dietary patterns, food security, and weight status: a study protocol - Amy Saxe-Custack; David Todem; James C. Anthony; Jean M. Kerver; Jenny LaChance; Mona Hanna-Attisha (BMC, 2022)
Abstract Background Although nutrients in fruits and vegetables are necessary for proper development and disease prevention, most US children consume fewer servings than recommended. Prescriptions for fruits and vegetables, written by physicians to exchange for fresh produce, address access and affordability challenges while emphasizing the vital role of diet in health promotion and disease prevention. Michigan's first fruit and vegetable prescription program (FVPP) exclusively for children was introduced in 2016 at one large pediatric clinic in Flint and expanded to a second clinic in 2018. The program provides one $15 prescription for fresh produce to all pediatric patients at every office visit. Prescriptions are redeemable at a year-round farmers' market or a local mobile market. The current study will assess the impact of this FVPP on diet, food security, and weight status of youth. Methods Demographically similar pediatric patient groups with varying levels of exposure to the FVPP at baseline will be compared: high exposure (> 24 months), moderate exposure (12-24 months), and no previous exposure. Data collection will focus on youth ages 8-16 years. A total of 700 caregiver-child dyads (one caregiver and one child per household) will be enrolled in the study, with approximately 200 dyads at clinic 1 (high exposure); 200 dyads at clinic 2 (moderate exposure), and 300 dyads at clinic 3 (no previous exposure). Children with no previous exposure will be introduced to the FVPP, and changes in diet, food security, and weight status will be tracked over two years. Specific aims are to (1) compare baseline diet, food security, and weight status between pediatric patients with varying levels of exposure to the FVPP; (2) measure changes in diet, food security, and weight status before and after never-before-exposed children are introduced to the FVPP; and (3) compare mean 12- and 24-month follow-up measures of diet, food security, and weight status in the initial no exposure group to baseline measures in the high exposure group. Discussion Completion of study aims will provide evidence for the effectiveness of pediatric FVPPs and insights regarding the duration and intensity of exposure necessary to influence change. Trial registration The study was registered through clinicaltrials.gov [ID: NCT04767282] on February 23, 2021.